2020
DOI: 10.7150/jca.36721
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcomes in adolescent and young adult patients with colorectal cancer -A multicenter large-scale cohort study

Abstract: Introduction: The prognosis of adolescent and young adult (AYA) patients with colorectal cancer (CRC) is still unclear. The aim of this study was to investigate the clinical features and prognosis in AYA patients compared with middle-aged patients. Methods: Participants were identified from a clinical database of the multicenter cohort in Japan. The AYA group was defined as those <40 years of age, whereas the middle-aged group was defined in 10-year ranges around the median age of all patients. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…The impact of age on the prognosis of CRC was still controversial [ 8 11 ], Zhao L [ 9 ]. et al reported a poor prognosis for CRC in younger patients, but Yang Z [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of age on the prognosis of CRC was still controversial [ 8 11 ], Zhao L [ 9 ]. et al reported a poor prognosis for CRC in younger patients, but Yang Z [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…et al reported that the prognosis of younger patients was similar to that of older patients. However, another study reported a better prognosis for younger patients [ 8 ]. We summarized the previous studies which reported the age on the outcomes of CRC patients in Table 5 [ 8 12 , 15 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the existing literature focuses exclusively on older adults and information is lacking regarding the unique HRQoL experiences of AYA CRC survivors [20]. AYA cancer survivors face distinct survivorship challenges due to their age and developmental life stage.…”
Section: Introductionmentioning
confidence: 99%